AB0430 MORTALITY IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS AND NEUROPSYCHIATRIC SYMPTOMS. (2nd June 2020) - Monahan, R.; Fronczek, R.; Eikenboom, J.; Middelkoop, H.; Beaart- van de Voorde, L. J. J.; Terwindt, G.; Van der Wee, N.; Rosendaal, F.; Huizinga, T.; Kloppenburg, M.; Steup-Beekman, G. M.
Abstract : Background: Little is known about mortality in patients with systemic lupus erythematosus (SLE) presenting with neuropsychiatric (NP) symptoms. Objectives: We aimed to evaluate all-cause and cause-specific mortality in patients with SLE and NP symptoms. Methods: All patients with the clinical diagnosis of SLE of 18 years and older that visited the tertiary referral NPSLE clinic of the Leiden University Medical Center between 2007-2018 and signed informed consent were included in this study. Patients were classified as NPSLE if NP symptoms were attributed to SLE and immunosuppressive or anticoagulant therapy was initiated, otherwise patients were classified as non-NPSLE. Municipal registries were checked for current status (alive/deceased). Electronical medical files were studied for clinical characteristics and cause of death. Standardized mortality ratios (SMRs) and 95% confidence intervals were calculated using data from the general Dutch population. In addition, a rate ratio (RR) was calculated using direct standardization to compare mortality in NPSLE with non-NPSLE patients. Results: 351 patients with the clinical diagnosis of SLE were included, of which 149 patients were classified as NPSLE (42.5%). Compared with the general population, mortality was increased five times in NPSLE (SMR 5.0, 95% CI: 2.6-8.5) and nearly four times in non-NPSLE patients (SMR 3.7, 95% CI: 2.2-6.0), as shown in Table 1 . Risk of death due to cardiovascular disease (CVD) was increased in non-NPSLE patients (SMR 6.2, 95% CI: 2.0-14.6) and an increased risk of death to infections was present in both NPSLE and non-NPSLE patients ((SMR 29.9, 95% CI: 3.5 – 105) and SMR 91.3 (95% CI: 18.8 – 266) respectively). However, mortality did not differ between NPSLE and non-NPSLE patients (RR 1.0, 95% CI: 0.5 – 2.0). Conclusion: Mortality was increased in both NPSLE and non-NPSLE patients in comparison with the general population, but there was no difference in mortality between NPSLE and non-NPSLE patients. Risk of death due to infections was increased in both groups. Disclosure of Interests: Rory Monahan: None declared, Rolf Fronczek: None declared, Jeroen Eikenboom: None declared, Huub Middelkoop: None declared, L.J.J. Beaart- van de Voorde: None declared, Gisela Terwindt: None declared, Nic van der Wee: None declared, Frits Rosendaal: None declared, Thomas Huizinga Grant/research support from: Ablynx, Bristol-Myers Squibb, Roche, Sanofi, Consultant of: Ablynx, Bristol-Myers Squibb, Roche, Sanofi, Margreet Kloppenburg: None declared, G.M. Steup-Beekman: None declared